Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer epidemiology, biomarkers & prevention, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLCAsb) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.
Keywords: Mesothelioma, Malignant; nádory plic; nemalobuněčný karcinom plic; Sensitivity and Specificity; senzitivita a specificita; Lung Neoplasms; regulace genové exprese u nádorů; Humans; lidé středního věku; Carcinoma, Non-Small-Cell Lung; MicroRNAs; Biomarkers, Tumor; Female; Aged; senioři; lidé; Asbestos; nádorové biomarkery; ženské pohlaví; Male; Middle Aged; Mesothelioma; Carcinogens; mezoteliom; karcinogeny; maligní mezoteliom; mikro RNA; azbest; mužské pohlaví; Gene Expression Regulation, Neoplastic